Determinação do valor de referência para o cortisol basal sérico em população pediátrica sem doença adrenal - Cristina Botelho Barra (2012)
The basal cortisol measurement reflects the hypothalamic-pituitary-adrenal activity. It is used in assessing the integrity of the axis response, mainly in patients undergoing long periods of glucocorticoid treatment, because they have a higher chance of adrenal suppression. In pediatrics, adrenal suppression should always be considered in children who received supraphysiologic glucocorticoid doses for more than two weeks. Under these conditions, there is an increased risk of adrenal crisis, even in the presence of moderate stressors. The cortisol values below the reference range are suggestive of adrenal dysfunction. Therefore, this evaluation may be crucial in the decision-making process. The same reference values of normal serum cortisol have been used, in practice, for adults and children. However, results obtained from an adult population may not be suitable for pediatric patients and can negatively impact the quality of this evaluation in childhood. Thus, the main objective of this study was to contribute to the assessment of basal cortisol levels in pediatric subjects. The assay method used by the reference laboratory for serum cortisol was the chemiluminescent enzyme immunoassay. The series was based on 120 reference individuals from 4-19 years old. The results obtained for cortisol were correlated with gender, age and pubertal maturation. The cortisol results profile was also studied for 95 children and adolescents from 0-19 years old, healthy or with persistent asthma and wheezing, prior to inhalation therapy. In the study, baseline serum cortisol increased with age and pubertal maturation. Serum cortisol showed no differences based on gender. Children from 0-3 years old with asthma and wheezing showed a great range of cortisol values, whereas older children showed less variation. The positive correlation between age and serum cortisol was observed only in children older than 3 years and it was more evident after 5 years old. Adolescents who were 16 to 19 years old had higher serum cortisol values than younger ones and also than those with incomplete pubertal development. The reference limits (2.5 and 97.5 percentiles) for the basal serum cortisol in the population of healthy subjects were: 2.97 g/dL [90% CI (1.44, 3.69)] and 23.4 g/dL [90% CI (16.3, 24.6)]. Thus, the interval for baseline serum cortisol of 4.46 to 22.7 g/dL being used up until now by the reference service was considered inappropriate for the pediatric population under study. The results presented here and the literature research suggest that reference intervals for serum cortisol should be determined specifically to the pediatric population.